1996
DOI: 10.1177/00220345960750021001
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cotinine Levels, Smoking, and Periodontal Attachment Loss

Abstract: Cigarette smoking and tobacco use have been the subjects of numerous studies for many years. Smoking has also been associated with periodontal disease. However, no relationship between a reliable biochemical marker and increased severity of the periodontal condition has yet been described. It was thus the aim of this study to apply the measurement of cotinine, the major metabolite of nicotine, as a quantitative method to assess levels of smoking, and to correlate serum levels of cotinine with severity of perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
107
0
6

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(126 citation statements)
references
References 43 publications
7
107
0
6
Order By: Relevance
“…Tobacco nicotine and its byproducts have a vasoconstrictive effect, not only on peripheral circulation but also on coronary, placental, and gingival blood vessels as well. 18 In addition, smoking may reduce the functional activity of leukocytes and macrophages in saliva and crevicular fluid, as well as decreasing chemotaxis and phagocytosis of blood and tissue polymorphonuclear leukocytes, thereby likely depressing phagocyte-mediated protective responses to periodontal pathogens. 19 The study also revealed that both plaque and gingival index scores were higher in the Periodontitis group compared to Group 1.…”
Section: Resultsmentioning
confidence: 99%
“…Tobacco nicotine and its byproducts have a vasoconstrictive effect, not only on peripheral circulation but also on coronary, placental, and gingival blood vessels as well. 18 In addition, smoking may reduce the functional activity of leukocytes and macrophages in saliva and crevicular fluid, as well as decreasing chemotaxis and phagocytosis of blood and tissue polymorphonuclear leukocytes, thereby likely depressing phagocyte-mediated protective responses to periodontal pathogens. 19 The study also revealed that both plaque and gingival index scores were higher in the Periodontitis group compared to Group 1.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, the utility of the finer measure will be limited to the abilities of the participants to gauge their true intake accurately (Gonzalez et al, 1996;Klesges et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be remembered that all retrospective studies are subject to recall bias, and while some studies have quantified lifetime exposure in packyears, current levels of smoking may not reflect past exposure. In one of the few studies which, to date, have measured cotinine, the severity of periodontal destruction, measured either as clinical attachment level or crestal bone height, was shown to be statistically positively correlated with serum cotinine levels (Gonzalez et al, 1996). Cotinine is the principle metabolite of nicotine and as such provides a valuable quantitative measure of smoking status.…”
mentioning
confidence: 99%